Meaning of Teseng Values in Constructing Farmer Accountability: A Phenomenological Study of Bugis Agriculture - Humaira Basri; Nispa sari; Sahrir Sahrir (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This research arises from the contrast between formal accountability in modern accounting and the local practice of the teseng system within the Bugis community, which is grounded in cultural values. The study aims to understand how the values embedded in teseng are interpreted in constructing farmer accountability. Methodology: A qualitative method with an interpretative phenomenological approach was employed, involving in-depth interviews and observations of farmers engaged in the teseng practice. Results: The findings indicate that accountability is not only constructed through formal mechanisms but also through cultural values such as lempu' (honesty), reso' (hard work), getteng' (steadfastness), and siri' (a sense of honor), which function as social and moral controls. This practice also reflects harmonious social relationships, mutual respect, and solidarity among actors. Findings: Teseng represents a form of culturally embedded accountability that emphasizes community involvement, trust, and moral values as the primary foundation for sustaining agricultural economic relationships. Novelty & Originality: This study offers novelty by integrating local Bugis cultural values into accountability discourse, a perspective rarely explored in conventional accounting research. Conclusions: The study concludes that teseng serves as a culturally grounded accountability model. Type of Paper: This paper is an empirical research paper.